Difference between revisions of "Math 22 Integration by Parts and Present Value"
Jump to navigation
Jump to search
(Created page with " '''Return to Topics Page''' '''This page were made by Tri Phan'''") |
(→Note) |
||
(8 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
+ | ==Integration by Parts== | ||
+ | |||
+ | Let <math>u</math> and <math>v</math> be differentiable functions of <math>x</math>. | ||
+ | |||
+ | <math>\int u dv=uv-\int v du</math> | ||
+ | |||
+ | '''Exercises''' Use integration by parts to evaluation: | ||
+ | |||
+ | '''1)''' <math>\int \ln x dx</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |Let <math>u=\ln x</math>, <math>>du=\frac{1}{x}dx</math> | ||
+ | |- | ||
+ | |and <math>dv=dx</math> and <math>v=x</math> | ||
+ | |- | ||
+ | |Then, by integration by parts: <math>\int \ln x dx=x\ln x-\int x\frac{1}{x}dx=x\ln x-\int dx=x\ln x -x +C</math> | ||
+ | |} | ||
+ | |||
+ | '''2)''' <math>\int xe^{3x}dx</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |Let <math>u=x</math>, <math>du=dx</math> | ||
+ | |- | ||
+ | |and <math>dv=e^{3x}dx</math> and <math>v=\frac{1}{3}e^{3x}</math> | ||
+ | |- | ||
+ | |Then, by integration by parts: <math>\int xe^{3x}dx=x\frac{1}{3}e^{3x} -\int\frac{1}{3}e^{3x} dx=x\frac{1}{3}e^{3x}-\frac{1}{9}e^{3x} +C </math> | ||
+ | |} | ||
+ | |||
+ | '''3)''' <math>\int x^2e^{-x}dx</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |Let <math>u=x^2</math>, <math>du=2xdx</math> | ||
+ | |- | ||
+ | |and <math>dv=e^{-x}dx</math> and <math>v=-e^{-x}</math> | ||
+ | |- | ||
+ | |Then, by integration by parts: <math>\int x^2e^{-x}dx=x^2(-e^{-x}) -\int-e^{-x}2x dx=-x^2e^{-x}+\int 2xe^{-x}dx </math> | ||
+ | |- | ||
+ | |Now, we apply integration by parts the second time for <math>\int 2xe^{-x}dx</math> | ||
+ | |- | ||
+ | |Let <math>u=2x</math>, <math>du=2dx</math> | ||
+ | |- | ||
+ | |and <math>dv=e^{-x}dx</math> and <math>v=-e^{-x}</math> | ||
+ | |- | ||
+ | |So <math>\int 2xe^{-x}dx=2x(-e^{-x})-\int -e^{-x} 2dx=-2xe^{-x}-e^{-x}+C</math> | ||
+ | |- | ||
+ | |Therefore, <math>\int x^2e^{-x}dx=-x^2e^{-x}-2xe^{-x}-e^{-x}+C</math> | ||
+ | |} | ||
+ | |||
+ | ==Note== | ||
+ | 1. Tabular integration technique (look it up) is convenient in some cases. | ||
+ | |||
+ | |||
+ | |||
[[Math_22| '''Return to Topics Page''']] | [[Math_22| '''Return to Topics Page''']] | ||
'''This page were made by [[Contributors|Tri Phan]]''' | '''This page were made by [[Contributors|Tri Phan]]''' |
Latest revision as of 16:22, 3 September 2020
Integration by Parts
Let and be differentiable functions of .
Exercises Use integration by parts to evaluation:
1)
Solution: |
---|
Let , |
and and |
Then, by integration by parts: |
2)
Solution: |
---|
Let , |
and and |
Then, by integration by parts: |
3)
Solution: |
---|
Let , |
and and |
Then, by integration by parts: |
Now, we apply integration by parts the second time for |
Let , |
and and |
So |
Therefore, |
Note
1. Tabular integration technique (look it up) is convenient in some cases.
This page were made by Tri Phan